KARAKTERISASI KEAUSAN KOMPOSIT CANGKANG KEMIRI DAN TEMPURUNG KELAPA SEBAGAI BAHAN PEMBUATAN KAMPAS REM (BRAKE PAD) - Juan Randy Simamora; Chandra Kurniawan (Universitas Quality, 2019)
The research has been conducted on the use of candlenut shells and coconut shells as composite materials in the manufacture of brake pads. The design of friction composite formulations is carried out based on four classes of friction material namely fillers, binders, reinforcing fibers and property modifiers with a fixed percentage based on weight. Comparison of the composition of Candlenut shell powder and coconut shell for each sample S-01 (35: 25) wt .-%, S-02 (30: 20) wt .-%, and S-03 (25: 15) wt. -%. From the results of data analysis, the values of water absorption for each sample were S-01 (0.00706%), S-02 (0.000496%), S-03 (0.00584%). The lowest wear test was found in the S-03 sample of 3.67 x 10-5 g / mm2.s. The SEM-EDS test results show the distribution of particles in different friction materials for each sample and show that carbon is present in approximately equal amounts in all formulations. The predominance of the presence of metals in brake linings includes: iron (Fe), magnesium (Mg), carbon (C), and aluminum (Al), silicon (Si), potassium (K)